A COMMENT ON "SOME ALTERNATIVES TO DEVELOPMENt" - Bryce, Murray (Dirasat in Economics and Business, 1968)
In reading Mr. Bryce's article on "Some Alternatives to Develop. ment ; Lessons for Libya" published in this mabazine, I found myse]f in disagreement with some of the views expressed, especially those touching upon Llhya. With due respect to Mr. Bryce's wide know. )edge in this field and with my limited knowledge on Libya I wish to make the following remarks. 1. The fir:;t point relates to Mr. Bryce's emphasis on the experien. ce of other countries and how, on such bases, Liby:i should avoid many unfavourable paths of development. I wish to que~tion the validity of how much one should draw from the experience .,f other countries as applied to a given country.